Get Answers to all your Questions

header-bg qa

Find and correct the errors in the following mathematical statements

Q11) 

( y - 3 ) ^ 2 = y ^ 2 -9

Answers (1)

best_answer

Our L.H.S.  is (y - 3 )^{2}  
                       = (y )^{2} + 2(y)(-3) + (-3)^{2}                                                                using    (a-b)^{2} = (a )^{2} + 2(a)(-b) + (-b)^{2}
                        = y^{2}- 6x + 9\neq  R.H.S.

Correct statement  is 

 (y - 3 )^{2} = y^{2}- 6x + 9

Posted by

Gautam harsolia

View full answer